Clinical characteristics and quality of life in Chinese patients with Parkinson's disease beyond 20 years. (3rd April 2018) - Ou, Ruwei; Hou, Yanbing; Song, Wei; Wei, Qianqian; Chen, Yongping; Cao, Bei; Yuan, Xiaoqin; Shang, Huifang
Abstract: Background: The number of Parkinson's disease (PD) patients with disease duration of more than 20 years (long disease duration PD,  LPD) is on the rise. Objectives: This study aims to describe the clinical profiles and the quality of life (QoL) of LPD patients from a cohort of the Chinese population. Methods: We compared 71 LPD subjects to 60 PD patients who died less than 20 years after the onset of PD (control PD,  CPD). A regression model was constructed to assess the determinants for 20 years survival and the QoL of LPD patients. Results: Compared to CPD patients, LPD patients exhibited a younger age at disease onset, higher total levodopa equivalent daily dose applications, more frequent motor complications, lower annual change in Unified PD Rating Scale (UPDRS) III score, as well as lower scores for 'sleep/fatigue' and 'mood/apathy' domains and higher score for 'sexual dysfunction' domain in the Non-Motor Symptom Scale (NMSS) ( p  < 0.05). Multivariate regression analyses indicated that a younger age at disease onset (OR = 0.520, 95%CI = 0.295–0.919, p  = 0.024), lower annual change in UPDRS III score (OR = 0.009, 95%CI = 0.001–0.246, p  = 0.005) and lower 'cardiovascular' score (OR = 0.552, 95%CI = 0.319–0.955, p  = 0.034) were associated with 20-year survival, while UPDRS III ( β  = 0.320, p  < 0.001) and NMSS ( β  = 0.549, p  < 0.001) scores were associated with the PD Questionnaire 39 score in LPD. Conclusions: The age at disease onset, rate of PD deterioration, and cardiovascular symptoms are the potential determinants for 20-year survival with PD. Both motor and non-motor disturbances contribute to the reduced QoL of LPD patients.